PENGEMBANGAN MODEL ASSESSMENT FOR LEARNING (AfL) MELALUI PENILAIAN TEMAN SEJAWAT UNTUK PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN PERSAMAAN GARIS LURUS DI MADRASAH TSANAWIYAH PONDOK PESANTREN MODERN ISLAM ASSALAAM SUKOHARJO - Kirbani, Kirbani (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT:The aims of this research were: (1) to determine whether the AFL with peer assessment on topics straight line equation can be applied in MTs PPMI Assalaam, (2) to know the influence of the application of the AFL with peer assessment in improving studentsâ achievement compare with direct instruction, (3) to know the influence of students ability to cooperate toward mathematics learning achievement of students in the subject of straight line equation, (4) to determine the effect of the application of the AFL with peer assessment in improving student achievement compare with direct instruction in terms of students ability to cooperate on subject of a straight line equation. The research was divided into two phases, namely the determination of the model development stage and the AfL with peer assessment are included in research and development. In this stage, data collection, prototype planning model, Focus Group Disscusion (FGD) were implemented and manufacture of prototype model then be tested. Tests carried out by 4 learning cycles. The next stage was to test the effectiveness of a model that includes quasi-experimental research design research 2Ã3. The population was eighth grade students of MTs PPMI Assalaam Sukoharjo first semester of the school year 2012/2013. Samples were divided into two groups, experimental and control groups. The data analysis technique used in this study was two-way analysis of variance unbalanced. Based on the result of the analysis, we can conclude that: (1) the model of the AFL with peer assessment can be applied in MTs PPMI Assalaam, (2) students taught using AFL with peer assessment have mathematics achievement better than students taught using direct instruction, (3) students with high cooperate ability levels have higher mathematics achievement than students with medium and low of ability to cooperate. While students with a medium level of ability to cooperate have a better achievement than students with a low level of ability to cooperate, (4) at all levels of ability to cooperate, students with applied learning AFL with peer assessment have better mathematics achievement than students with direct learning.Key words : Assessment, Assesment for Learning (AfL), Peer Assessment, Ability to Cooperate